Kontinuitas Apokaliptik: Kajian Intertekstual Figur Anak Manusia dalam Daniel 7:13-14 dan Kitab Wahyu - Andri Harvijanto; Marhareni Pangeti (Sekolah Tinggi Teologi Nusantara, 2026)
Debate concerning the identity of the mysterious figure of the ‘Son of Man’ in Daniel 7:13–14. The methodology employed is qualitative, utilising a literature review approach combined with Richard B. Hays’s intertextual analysis to trace the ‘echoes’ of the text of Daniel within the narrative of Revelation. But how does the Book of Revelation, through an intertextual approach, identify Jesus Christ as the figure of the “Son of Man” in Daniel 7:13–14 and affirm his Christological continuity and transformation within an eschatological context? Book of Revelation systematically identifies the glorified Jesus Christ with the figure of the “Son of Man”. This continuity is clearly evident through the use of similar terminology in Revelation 1:13 and 14:14, as well as the attribution of the divine attributes of the Ancient of Days to Christ. The study concludes that John undertook a Christological transformation that positions Christ as the definitive fulfilment of Daniel’s prophecy, holding universal authority and eschatological victory over the forces of evil. The implications of this research affirm that New Testament Christology must be understood in continuity with the Old Testament apocalyptic tradition, in which Jesus Christ is positioned as the definitive fulfilment of the figure “Son of Man” who possesses divine authority and a universal eschatological role.AbstrakPerdebatan akademis mengenai identitas figur misterius